2008
DOI: 10.1097/sla.0b013e31815f6e5b
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Portal Vein Embolization for Major Liver Resection

Abstract: PVE is a safe and effective procedure in inducing liver hypertrophy to prevent postresection liver failure due to insufficient liver remnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
395
2
25

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(446 citation statements)
references
References 37 publications
11
395
2
25
Order By: Relevance
“…Portal vein embolization induces atrophy of the liver to be resected and hypertrophy of the liver that will remain (i.e. increases the future liver remnant) (18). Similarly, two-stage hepatectomies in CRLM involve delayed re-hepatectomy after hypertrophy of the residual liver and may be used for large bilateral lesions in which a one stage resection of all the involved segments would lead to liver failure (19).…”
Section: Discussionmentioning
confidence: 99%
“…Portal vein embolization induces atrophy of the liver to be resected and hypertrophy of the liver that will remain (i.e. increases the future liver remnant) (18). Similarly, two-stage hepatectomies in CRLM involve delayed re-hepatectomy after hypertrophy of the residual liver and may be used for large bilateral lesions in which a one stage resection of all the involved segments would lead to liver failure (19).…”
Section: Discussionmentioning
confidence: 99%
“…PVE can be performed using either transileocolic portal vein embolization or percutaneous transhepatic portal vein embolization (preferred). On average, PVE produces a 25-80 % increase in the absolute volume of the non-embolized liver [11,[38][39][40]. PVE has also been shown to be safe and effective in patients that are currently undergoing neoadjuvant chemotherapy.…”
Section: Designing Strategies For Conversion To Resectable Diseasementioning
confidence: 99%
“…After a median of 30 days, patients on neoadjuvant chemotherapy were found to have similar liver hypertrophy compared to patients not undergoing chemotherapy. A large meta-analysis by Abulkhir et al identified 37 studies with 1088 patients [38]. Overall morbidity for PVE was 2.2 % and 85 % of patients underwent laparotomy with 83 % resectability in patients who underwent PVE.…”
Section: Designing Strategies For Conversion To Resectable Diseasementioning
confidence: 99%
“…При этом через 7-8 нед после редукции кровотока в правой ветви во-ротной вены наступает гипертрофия остающихся от-делов печени, что позволяет выполнить оперативное вмешательство в радикальном объеме. Однако реа-лизовать 2-й этап запланированной двухэтапной ре-зекции печени удается не более чем у 70-75% паци-ентов, что, в первую очередь, связано с отсутствием гипертрофии остающихся отделов печени (FLR) [1][2][3]. Исследователями было доказано, что при FLR мень-ше 20% при состоятельной паренхиме печени и 40% при функциональном (неоадъювантная химиотера-пия, цирроз) поражении печени реализация хирур-гических вмешательств сопряжена с крайне высоким риском развития печеночной недостаточности [4][5][6].…”
Section: Introductionunclassified